Comunidade conscienciológica: voluntariado, migração e territorialidades - Silva, Cristiane Ferraro Gilaberte da (2020)
This doctoral research focuses on the conscientiological community. It is located in the Cognópolis neighborhood, in Foz do Iguaçu, in the west region of Parana State, Brazil. The importance of this study is centred on better understanding the characteristics of one of so many socio-cultural groups present in the Triple Border Region Argentina-Brazil-Paraguay, since 1995. The guiding question of the study was: what is the conscientiological community? When reconstructing its historicity, the conscientiological community began to be delimited from three theoretical dimensions: institutional volunteering, migration and territoriality. The first theoretical dimension, voluntary work and issues involving the so-called Third Sector, was addressed in dialogue with Antonio Albuquerque (2006), Paula Bonfim (2010), Carlos Eduardo Cavalcante (2013), Ricardo ALG Dias (2010), Vasco Almeida (2011), Henrique Pinto (2011) and Bruno Barcelos Morais (2019), in addition to data from the Brazilian Institute of Geography and Statistics (IBGE). The second theoretical dimension, migration, was supported by the views of researchers Fernando Luís Machado (2002), Maria Lucinda Fonseca (2005), Carmem Lussi (2015), Michaela Benson (2009; 2016), Karen O'Reilly ( 2009; 2016), Russell King (2012), LAG Moss (2006), Mari Korpela (2014) and Noel B. Salazar (2014). IBGE data were also used in order to compare the information collected about conscientious migrants. And the third theoretical dimension, territoriality, was discussed from the interlocution with geographers Claude Raffestin (1993), Rogério Haesbaert (2007; 2010) and Marcos Aurélio Saquet (2015). It is an interdisciplinary study, using the theoreticalmethodological contribution of micro-history and thematic oral research. The research sources were questionnaires, interviews and documents, such as minutes, reports, bylaws, among others. The final considerations were elaborated from the set of evidence that appeared in the text, making it possible to outline conceptualization and characterization of the conscientiological community. It can be mentioned that the conscientiological community was triggered by institutional volunteering and was taking shape from the territorial and migratory dynamics. The initial relationships of volunteer colleagues became more complex when they became neighborhood relationships, integrating family, friendships and professional colleagues. It was concluded that this community is constituted in a social and cultural phenomenon characterized with hybrid traits of the traditional and the modern, at the same time, with typical community problems, on the other hand, with a strong institutionalized character, in the way of an “institutionalized community”, but not limited to this dimension.